Oxide solid electrolyte, preparation method thereof and solid-state battery

By adopting oxide solid electrolyte with polyanion cluster structure in lithium-ion batteries and using the synergistic mechanism of fluoride ions and polyanion, the complex and cost-effective preparation of liquid electrolytes and inorganic solid electrolytes is solved, and a high-performance and low-cost solid battery technology is achieved.

CN119890436AActive Publication Date: 2025-04-25SHENZHEN MSU-BIT UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510380243.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

The liquid electrolytes in existing lithium-ion batteries are flammable, resulting in safety hazards; while the preparation process of inorganic solid electrolytes is complex, costly, and sensitive to air humidity.

Method used

The oxide solid electrolyte with polyanion cluster structure is adopted, and the degree of electron-ion coupling is reduced through the synergistic mechanism of fluoride ions and polyanion, and the ion conductivity is improved.

Benefits of technology

It significantly improves the room temperature ion conductivity of solid electrolytes, reduces the migration energy barrier of lithium ions, improves the safety and performance of the battery, and is cheap, suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890436A_ABST
    Figure CN119890436A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solid-state battery preparation, and discloses an oxide solid-state electrolyte, a preparation method thereof and a solid-state battery. The oxide solid electrolyte is a mixture solid electrolyte, the chemical formula of the oxide solid electrolyte is A2MF, and A is any one of Li, Na and K elements; m is any one or more of BO3 < 3->, CO3 < 2->, NO3 <->, NO2 <->, SiO4 < 4->, SiO3 < 2->, PO33 <->, PO4 < 3->, SO4 < 2->, SO3 < 2->, ClO4 <->, ClO3 <->, CrO4 < 2->, MnO4 < 2-> and TeO4 < 2->, and meanwhile, valence balancing of the chemical formula is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state battery preparation, and specifically relates to an oxide solid electrolyte and a preparation method thereof, and a solid-state battery. Background Art

[0002] Lithium-ion batteries are now widely used in new energy vehicles, data centers, communication base stations, major equipment, energy storage power stations and other fields due to their excellent energy density. In the past two centuries, the academic community has mainly focused on the research of lithium-ion batteries based on liquid electrolytes. Although traditional liquid electrolytes have high ion conductivity, organic electrolytes are flammable and are prone to combustion or even explosion accidents when the battery is thermally runaway. In contrast, all-solid-state lithium batteries use solid electrolytes (SSE) to replace liquid electrolytes and diaphragms, avoiding the use of organic solvents and improving the safety of lithium-ion batteries. Generally speaking, solid electrolytes can be divided into three categories: polymer solid electrolytes, composite solid electrolytes and inorganic solid electrolytes. Among them, inorganic solid electrolytes can be specifically divided into sulfide solid electrolytes, oxyhalide solid electrolytes and oxide solid electrolytes. Sulfide solid electrolytes have attracted widespread attention for their excellent ionic conductivity and excellent low-temperature performance. However, the manufacturing process of sulfide solid electrolytes is strict, the chemical stability is poor, they are extremely sensitive to air humidity, and they can react with water vapor to produce highly toxic H2S gas. Oxyhalide solid electrolytes have the characteristics of high ionic conductivity and strong stability. In addition, they have high room temperature conductivity and are less sensitive to humidity than sulfides. However, the raw materials required for the preparation of oxyhalide solid electrolytes involve transition metal elements such as Ta and Y. The high cost of raw materials limits the large-scale application of oxyhalide solid electrolytes. Oxide solid electrolytes have the advantages of both sulfide and oxyhalide solid electrolytes and are compatible with high-voltage positive electrodes. The ionic conductivity of partially doped and modified oxide solid electrolytes can also reach 10 at room temperature. -3 S / cm. However, the preparation process of oxide solid electrolytes is relatively complicated and requires a higher sintering temperature to densify them. Summary of the invention

[0003] In order to overcome the shortcomings and deficiencies in the prior art, the primary purpose of the present invention is to provide an oxide solid electrolyte; the oxide solid electrolyte has a unique polyanion cluster structure, and the lattice distortion brought about by this structure is conducive to constructing a high entropy environment and providing a variety of possible ion transmission channels, thereby reducing the energy barrier of ion migration; in addition, by adjusting the doping ratio of the two polyanions, the degree of lattice distortion can be affected, which can further promote ion transmission.

[0004] Another object of the present invention is to provide a method for preparing the above-mentioned oxide solid electrolyte; this method integrates a variety of technical means for improving the ionic conductivity of the solid electrolyte, through the synergistic mechanism of electrons and ions, that is, fluoride ions and polyanions can reduce the degree of electron-ion coupling through local field effects, reducing the Coulomb interaction of the anion skeleton in the lattice with lithium ions, which is beneficial to the rapid migration of lithium ions in the lattice, and ultimately significantly improves the ionic conductivity of the electrolyte.

[0005] Another object of the present invention is to provide an application of the above-mentioned oxide solid electrolyte; the solid electrolyte material prepared by the present invention is not only low-cost, but also has high ionic conductivity and good stability, is suitable for large-scale production, and is suitable for wide application in the next generation of solid-state batteries. It is a new technical path for developing low-cost, high-performance solid-state batteries.

[0006] Another object of the present invention is to provide a solid-state battery made of the above-mentioned oxide solid electrolyte.

[0007] The purpose of the present invention is achieved through the following technical solutions: An oxide solid electrolyte, wherein the chemical formula of the oxide solid electrolyte is A2MF, wherein A is any one of Li, Na and K elements; M is BO3 3- 、CO3 2- 、NO3 - 、NO2 - 、SiO4 4- 、SiO3 2- PO3 3- PO4 3- 、SO4 2- 、SO3 2- 、ClO4 - 、ClO3 - 、CrO4 2- 、MnO4 2- ,TeO4 2- Any one or more of the above, while ensuring the valence balance of the chemical formula.

[0008] The oxide solid electrolyte is a mixed solid electrolyte. The raw materials used do not have the properties of ion conductors, while the solid electrolyte obtained by this design has the properties of ion conductors. The oxide solid electrolyte presents irregular particles with a particle size of 10nm~100μm. The room temperature ionic conductivity of the oxide solid electrolyte reaches 10 -5 Scm -1 above.

[0009] Specifically, for Li-based oxide solid electrolytes, the chemical composition is Li2MF (M is BO3 3-、CO3 2- 、NO3 - 、NO2 - 、SiO4 4- 、SiO3 2- PO3 3- PO4 3- 、SO4 2- 、SO3 2- 、ClO4 - 、ClO3 - 、CrO4 2- 、MnO4 2- and TeO4 2- One or more of the above, while ensuring the valence balance of the chemical formula).

[0010] For Na-based oxide solid electrolytes, the chemical composition is Na2MF (M is BO3 3- 、CO3 2- 、NO3 - 、NO2 - 、SiO4 4- 、SiO3 2- PO3 3- PO4 3- 、SO4 2- 、SO3 2- 、ClO4 - 、ClO3 - 、CrO4 2- 、MnO4 2- and TeO4 2- One or more of the above, while ensuring the valence balance of the chemical formula).

[0011] For K-based oxide solid electrolyte, its chemical composition is K2MF (M is BO3 3- 、CO3 2- 、NO3 - 、NO2 - 、SiO4 4- 、SiO3 2- PO3 3- PO4 3- 、SO4 2- 、SO3 2- 、ClO4 - 、ClO3 - 、CrO4 2- 、MnO4 2- and TeO4 2- One or more of the above, while ensuring the valence balance of the chemical formula).

[0012] The above-mentioned method for preparing an oxide solid electrolyte comprises the following steps: Under a dry environment, alkali metal fluoride AF and alkali metal salt AM are weighed as starting raw materials, put into a homogenizer and mix them thoroughly, the mixture is transferred into a container, placed in a high-temperature furnace and heated to 100-300°C at a heating rate of 10-20°C / min for pre-sintering; the pre-sintered product is placed in a ball mill, and a wet grinding solvent is added for ball milling, the ball milling parameters are set to a rotation speed of 200rpm-600rpm, and the ball milling time is 6-12 hours; the material obtained after ball milling is loaded into a mold and a pressure of 2t-8t is applied; then the pressurized material is transferred to a high-temperature furnace and sintered at 300°C-700°C, and the obtained solid is crushed and ground after cooling to finally obtain an oxide solid electrolyte.

[0013] The molar ratio of the alkali metal fluoride AF to the alkali metal salt AM is 1:1; A in both AF and AM is any one of Li, Na and K; AM is A3BO3 3- 、A2CO3 2- 、ANO3 - 、ANO2 - 、A4SiO4 4- 、A2SiO3 2- 、A3PO3 3- 、A3PO4 3- 、A2SO4 2- 、A2SO3 2- 、AClO4 - 、AC1O3 - 、A2CrO4 2- 、A2MnO4 2- and A2TeO4 2- When AM is a plurality of the above alkali metal salts, the amount of each alkali metal salt is used to ensure the valence balance of the chemical formula of the final oxide solid electrolyte.

[0014] The wet grinding solvent is one of ethanol, isopropanol, n-hexane, acetone, methanol, ethylene glycol, cyclohexane, dichloromethane and n-heptane; The "dry environment" refers to an environment where the relative humidity is less than 30% or the dew point is less than -2°C.

[0015] The above-mentioned application of an oxide solid electrolyte in the preparation of a solid-state battery.

[0016] A solid-state battery comprising the above-mentioned oxide solid-state electrolyte.

[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) This invention innovatively integrates multiple methods to improve the ionic conductivity of solid electrolytes to prepare a type of mixed oxide solid electrolytes; and provides a control scheme to achieve an ionic conductivity of 10 at room temperature. -5 Scm -1 above.

[0018] (2) The preparation process of the present invention introduces highly electronegative fluoride ions. The high electronegativity of fluoride ions can induce polarization of neighboring cations, weakening the strong bond between lithium ions and the crystal lattice. Fluoride ions are singly charged anions with a small ionic radius (≈1.33 Å) and a low charge density, which can further weaken the binding effect on lithium ions. In addition, fluoride ions can form a stable LiF layer at the electrolyte / electrode interface, reducing side reactions and promoting uniform deposition of lithium ions.

[0019] (3) The present invention adopts an innovative design of a polyanion cluster structure. The electrolyte material prepared by the present invention has a unique polyanion cluster structure. The polyanions have a large volume and dispersed negative charge, which can reduce the charge density in local areas of the lattice. This dispersion effect weakens the Coulomb attraction between lithium ions and the lattice, reducing the migration energy barrier of lithium ions. In addition, the mixed structure of polyanions of different sizes can induce lattice distortion. Such a high-entropy environment brings abundant lithium ion hopping sites, which can effectively reduce the migration energy barrier of lithium ions. In addition, by adjusting the addition ratio of multiple polyanions, the degree of lattice distortion can be flexibly controlled, which can further optimize the ion migration path.

[0020] (4) The synergistic mechanism of electrons and ions designed in the present invention, namely, fluoride ions and polyanions can reduce the degree of electron-ion coupling through local field effects, reducing the Coulomb interaction of the anion skeleton in the lattice with lithium ions, which is conducive to the rapid migration of lithium ions in the lattice, and ultimately significantly improves the ionic conductivity of the electrolyte.

[0021] (5) The difference between the solid electrolyte designed by the method of the present invention and the solid electrolyte prepared by the existing method is that the composition of the solid electrolyte designed by the method is a mixture of several substances that do not have ion conductor properties. This mixture solid electrolyte has low preparation cost, efficient process, excellent performance, and has great application potential.

[0022] (6) The raw materials used in the present invention are cheap and readily available, which significantly reduces production costs and provides economic feasibility for large-scale commercial applications. At the same time, the synthesis process conditions of the present invention are mild and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1The AC impedance spectra of the raw materials and products prepared by the present invention in Example 1, where the left figure is the AC impedance spectra of the raw materials LiF and Li2SO4, and the right figure is the AC impedance spectra of the prepared product Li2(SO4) 0.5 F and Li2(SO4) 0.3 (CO3) 0.2 AC impedance spectrum of F.

[0024] Figure 2 The AC impedance spectra of the products prepared by the mechanical mixing method in Example 1, wherein the left figure is the AC impedance spectrum of the product LiF•Li2SO4, and the right figure is the AC impedance spectrum of the product LiF•Li2SO4•Li2CO3.

[0025] Figure 3 The product Li2(SO4) prepared by the present invention in Example 1 0.5 XRD patterns of F and raw materials (left), LiF•Li2SO4 prepared by mechanical mixing method and Li2(SO4) prepared by the present invention 0.5 FTIR spectrum of F (right).

[0026] Figure 4 The product Li2(SO4) prepared by the present invention in Example 1 0.5 F and Li2(SO4) 0.3 (CO3) 0.2 F's lithium metal symmetric battery cycling test results.

[0027] Figure 5 The AC impedance spectra of the raw materials and products prepared by the present invention in Example 2, where the left figure is the AC impedance spectra of the raw materials NaF, Na4SiO4 and NaNO3, and the right figure is the AC impedance spectra of the prepared product Na2(SiO4) 0.1 (NO3) 0.6 F and Na2(SiO4) 0.2 (NO3) 0.2 AC impedance spectrum of F.

[0028] Figure 6 The AC impedance spectra of the products prepared by the mechanical mixing method in Example 2, wherein the left figure is the AC impedance spectrum of the product NaF•Na4SiO4•NaNO3-1, and the right figure is the AC impedance spectrum of the product NaF•Na4SiO4•NaNO3-2. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0030] Embodiment 1: In a dry environment (relative humidity less than 30%), weigh 1 mol LiF and 0.5 mol Li2SO4 as raw materials to prepare Li2(SO4) 0.5 F, weigh 1 mol LiF, 0.3 mol Li2SO4 and 0.2 mol Li2CO3 as raw materials to prepare Li2(SO4) 0.3 (CO3) 0.2 F. The specific steps of the preparation method are as follows: put the raw materials into a homogenizer and mix them thoroughly, then transfer the mixture into a container, place it in a high-temperature furnace and heat it to 300°C at a heating rate of 10°C / min for pre-sintering; put the product obtained after pre-sintering into a ball mill, add ethanol as a wet grinding solvent, and perform ball milling at a speed of 500rpm for 12 hours, and put the material obtained after ball milling into a mold and apply a pressure of 2t; then transfer the pressurized material to a high-temperature furnace and sinter it at a temperature of 600°C, and after cooling, crush and grind the obtained solid to finally obtain the following product: oxide solid electrolyte Li2(SO4) 0.5 F and Li2(SO4) 0.3 (CO3) 0.2 F.

[0031] The raw materials and products used in the preparation were subjected to impedance tests respectively. The AC impedance spectra were as follows: Figure 1 shown; from Figure 1 It can be seen that the raw materials LiF and Li2SO4 themselves have no conductivity, and Li2CO3 is also known to have no conductivity. However, the product Li2(SO4) prepared by the scheme of the present invention has 0.5 F and Li2(SO4) 0.3 (CO3) 0.2 F has the property of conducting electricity, indicating that the target product is successfully synthesized and is a mixture. Figure 1 It can also be seen from the right figure that the double polyanion solid electrolyte (Li2(SO4) 0.3 (CO3) 0.2 F) Compared with the single polyanion solid electrolyte (Li2(SO4) 0.5 F) shows lower impedance, indicating that anion CO3 2- Doping can effectively improve lithium ion conductivity.

[0032] In order to demonstrate that the mixed oxide solid electrolyte prepared by the present invention has better performance, the existing mechanical mixing method is used to prepare the product for comparative experiment; the specific steps of the mechanical mixing method are: first put the weighed raw materials into an agate mortar for premixing, and then put the premixed sample into a ball mill for ball milling, and the ball milling and mixing are uniform to obtain the product. The product prepared by mechanical mixing method using 1 molLiF and 0.5 mol Li2SO4 as raw materials is recorded as LiF•Li2SO4; the product prepared by mechanical mixing method using 1 molLiF, 0.3 molLi2SO4 and 0.2 molLi2CO3 as raw materials is recorded as LiF•Li2SO4•Li2CO3; the products LiF•Li2SO4 and LiF•Li2SO4•Li2CO3 prepared by the mechanical mixing method are subjected to impedance testing, and the results are as follows Figure 2 shown. Figure 2 and Figure 1 By comparison, it can be seen that the product prepared by the existing mechanical mixing method has worse conductivity than the product prepared by the solution of the present invention, has almost no impedance value, and has no commercial value.

[0033] The product obtained by this scheme was subjected to XRD test, and the data are shown in Figure 3 (left); from Figure 3 (Left) As can be seen, the product Li2(SO4) 0.5 The diffraction peak positions of F and the raw materials LiF and Li2SO4 are basically unchanged, indicating that the lattice structure of the synthesized product has not changed significantly. The product Li2(SO4) 0.5 F is just a mixture. To further determine whether the product is synthesized, the raw material, LiF•Li2SO4 prepared by mechanical mixing method and the product Li2(SO4) prepared by this scheme are mixed. 0.5 F was tested by FTIR, the data is shown in Figure 3 (Right). The results show that the product prepared by this scheme is better than the product prepared by mechanical mixing method in the range of 2000~4000cm -1 A new peak is generated in the range of , which is presumed to be the FNO oscillation peak, indicating that the product prepared by this scheme forms a new coordination, which may be the reason why the ionic conductivity of the sample prepared by the scheme of the present invention is better than that of the sample prepared by the mechanical preparation method.

[0034] Finally, the product Li2(SO4) prepared by the present invention is 0.5 F and Li2(SO4) 0.3 (CO3) 0.2 F solid electrolyte assembled lithium metal symmetric battery, test results show that Li2(SO4) 0.3 (CO3) 0.2The lithium metal symmetric battery assembled with F solid electrolyte has low polarization voltage, higher limiting current density and lithium cycling stability. Figure 4 .

[0035] Embodiment 2: In a dry environment (relative humidity less than 30%), weigh 1 mol NaF, 0.1 mol Na4SiO4 and 0.6 mol NaNO3 to prepare Na2(SiO4) 0.1 (NO3) 0.6 F, weigh 1 mol NaF, 0.2 mol Na4SiO4 and 0.2 mol NaNO3 to prepare Na2(SiO4) 0.2 (NO3) 0.2 F. Put the raw materials into a homogenizer and mix them thoroughly; transfer the mixture into a container, place it in a high-temperature furnace and heat it to 200℃ at a heating rate of 10℃ / min for pre-sintering; put the product obtained after pre-sintering into a ball mill, add ethanol as a wet grinding solvent, and perform ball milling at a speed of 500rpm for 8 hours, and put the material obtained after ball milling into a mold and apply a pressure of 2t; then transfer the material after applying pressure to a high-temperature furnace and sinter it at a temperature of 700℃, and after cooling, crush and grind the obtained solid to finally obtain the following product: oxide solid electrolyte Na2(SiO4) 0.1 (NO3) 0.6 F. Na2(SiO4) 0.2 (NO3) 0.2 F.

[0036] The raw materials and products used in this example were subjected to AC impedance tests, and the AC impedance spectra were as follows: Figure 5 As shown. Figure 5 It can be seen that the raw materials NaF, Na4SiO4 and NaNO3 themselves do not have conductivity, and the product Na2(SiO4) prepared by the scheme of the present invention 0.1 (NO3) 0.6 F and Na2(SiO4) 0.2 (NO3) 0.2 F has a certain ionic conductivity, indicating that the synthesis is successful. Compared with Na2(SiO4) 0.1 (NO3) 0.6 F and Na2(SiO4) 0.2 (NO3) 0.2 It can be seen from the impedance data of F that the ionic conductivity of the sample can be effectively changed by adjusting the ratio of the two polyanions.

[0037] In order to demonstrate that the mixed oxide solid electrolyte prepared by the present invention has better performance, the existing mechanical mixing method was used to prepare the product for comparative experiments; the specific steps of the mechanical mixing method are: first, the weighed raw materials are placed in an agate mortar for premixing, and then the premixed sample is placed in a ball mill for ball milling, and the ball milling and mixing are uniform to obtain the product. The product prepared by mechanical mixing using 1 mol NaF, 0.1 mol Na4SiO4 and 0.6 mol NaNO3 as raw materials is recorded as NaF•Na4SiO4•NaNO3-1, and the product prepared by mechanical mixing using 1 mol NaF, 0.2 mol Na4SiO4 and 0.2 mol NaNO3 as raw materials is recorded as NaF•Na4SiO4•NaNO3-2. The NaF•Na4SiO4•NaNO3-1 and NaF•Na4SiO4•NaNO3-2 prepared by the mechanical mixing method are subjected to impedance tests, and the results are as follows: Figure 6 As shown. Figure 5 and Figure 6 It can be seen that the product prepared by the existing mechanical mixing method has no impedance value or the impedance is unstable, and the performance is far lower than the product prepared by the solution of the present invention.

[0038] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An oxide solid electrolyte, characterized in that: The chemical formula of the oxide solid electrolyte is A2MF, wherein A is any one of Li, Na and K elements; M is BO3 3- 、CO3 2- 、NO3 - 、NO2 - 、SiO4 4- 、SiO3 2- PO3 3- PO4 3- 、SO4 2- 、SO3 2- 、ClO4 - 、ClO3 - 、CrO4 2- 、MnO4 2- and TeO4 2- Any one or more of the above, while ensuring the valence balance of the chemical formula.

2. An oxide solid electrolyte according to claim 1, characterized in that: The oxide solid electrolyte is a mixed solid electrolyte with irregular particles and a particle size of 10nm~100μm; the room temperature ionic conductivity of the oxide solid electrolyte reaches 10 -5 S cm -1 above.

3. A method for preparing an oxide solid electrolyte according to claim 1, characterized in that The steps include: Under a dry environment, alkali metal fluoride AF and alkali metal salt AM are weighed as starting raw materials, put into a homogenizer and mix them thoroughly, transfer the mixture into a container, place it into a high-temperature furnace and heat it to 100-300°C at a heating rate of 10-20°C / min for pre-sintering; put the pre-sintered product into a ball mill, add a wet grinding solvent for ball milling, set the ball milling parameters to a speed of 200rpm-600rpm, and the ball milling time is 6-12 hours; put the material obtained after ball milling into a mold and apply a pressure of 2t-8t; then transfer the pressurized material to a high-temperature furnace and sinter it at 300°C-700°C, and crush the obtained solid after cooling, Grind and finally obtain the oxide solid electrolyte.

4. The method for preparing an oxide solid electrolyte according to claim 3, characterized in that: The molar ratio of the alkali metal fluoride AF to the alkali metal salt AM is 1:1; the starting material AF and A in the AM are simultaneously any one of Li, Na and K elements; the AM is A3BO3 3- 、A2CO3 2- 、ANO 3- 、ANO 2- 、A4SiO4 4- 、A2SiO3 2- 、A3PO3 3- 、A3PO4 3- 、A2SO4 2- 、A2SO3 2- 、AC1O 4- 、AC1O 3- 、A2CrO4 2- 、A2MnO4 2- and A2TeO4 2- When AM is a plurality of the above alkali metal salts, the amount of each alkali metal salt is used to ensure the valence balance of the chemical formula of the final oxide solid electrolyte.

5. The method for preparing an oxide solid electrolyte according to claim 3, characterized in that: The wet grinding solvent is one of ethanol, isopropanol, n-hexane, acetone, methanol, ethylene glycol, cyclohexane, dichloromethane and n-heptane.

6. The method for preparing an oxide solid electrolyte according to claim 3, characterized in that: The dry environment refers to an environment with a relative humidity of less than 30% or a dew point of less than -2°C.

7. An application of the oxide solid electrolyte according to claim 1, characterized in that: This application uses the oxide solid electrolyte to prepare a solid-state battery.

8. A solid-state battery, characterized in that The solid-state battery comprises an oxide solid-state electrolyte as claimed in claim 1.

Citation Information

Patent Citations

  • Sodium ion solid electrolyte and preparation method thereof

    CN109687017A

  • Polyanion solid electrolyte, preparation method thereof and solid-state battery

    CN119560625A

  • Solid electrolyte, electrode, and solid electrolyte battery

    JP2025020901A